Menggagas Hak Kekayaan Intelektual Perspektif Hukum Islam ke dalam Hukum Nasional - Triana, Nita (Al-Manahij: Jurnal Kajian Hukum Islam, 2018)
This study aims to describe and analyze Intellectual Property Rights (IPR) under the rules of Trade-Related Aspects of Intellectual Property Rights (TRIPs) which are in several respects different from the laws that live in Indonesia. Therefore, it is necessary to initiate Intellectual Property Rights Law that is in accordance with the values that live in Indonesia, the majority of which are Muslim communities. The results of this study illustrate that the legal protection of the owners of InÂtellectual Property Rights (IPR) in Indonesia has been regulated in various laws and regulations that are included in the Intellectual Property Rights Law system. These regulations must refer strictly to the TRIPs Agreement. The Intellectual Property Rights regime with the rules of TRIPs has two sides in the protection of intellectual property rights, on the one hand it protects individual interests from piracy and theft of intellectual property, but on the other hand empirically this leÂgal protection greatly benefits developed countries. Based on this, the Intellectual Property Rights Law must be rebuilt with the source of material law originating from values that live in Indonesian society, namely Islamic law.